2014
DOI: 10.1037/arc0000008
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory examination of pain threshold and tolerance among nonsuicidal self-injurers with and without self-punishing motivations.

Abstract: Nonsuicidal self-injury (NSSI), which refers to self-directed destruction of bodily tissue in the absence of suicidal intent (e.g., cutting, carving, burning) is a widespread health concern. Recent research suggests that individuals who engage in NSSI have heightened tolerances for pain relative to noninjurers, but little attention has been given to how self-injurers overcome the pain involved in self-directed injury. Understanding the process through which self-injurers tolerate pain, however, may have import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 68 publications
1
41
0
3
Order By: Relevance
“…Of these, two included measures of psychiatric symptomatology (Glenn et al, 2014;Hamza et al, 2014), but only Glenn and colleagues (2014) reported the results: 64.6% of the sample met the criteria for at least one psychiatric disorder, with anxiety, mood disorders, and alcohol and substance use disorders being the most prevalent. There was no effect of psychiatric symptomatology upon pain threshold or endurance.…”
Section: Sample Populationmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, two included measures of psychiatric symptomatology (Glenn et al, 2014;Hamza et al, 2014), but only Glenn and colleagues (2014) reported the results: 64.6% of the sample met the criteria for at least one psychiatric disorder, with anxiety, mood disorders, and alcohol and substance use disorders being the most prevalent. There was no effect of psychiatric symptomatology upon pain threshold or endurance.…”
Section: Sample Populationmentioning
confidence: 99%
“…The majority of participants within the community sample studies endorsed cutting and self-hitting as the most common types of NSSI (Franklin et al, 2010;Glenn et al, 2014;Hamza et al, 2014) and within the latter two studies, self-pinching, severe scratching as well as self-hitting were also reported. Little information was given by Bohus et al…”
Section: Type Of Nssimentioning
confidence: 99%
See 3 more Smart Citations